Esquisse d'un Salon. - Lambert, Jean-Clarence; Lassaigne, Jacques (Paris : Galerie Denise René, 1963)
Adams, Robert ; Agam, Yaacov ; Albers, Josef ; Andersen, Mogens ; Anthoons, Willy ; Arcay, Wilfredo ; Arp, Hans (Jean) ; Baertling, Olle ; Bally, Théodore ; Billy, Lucien ; Bonfanti, Arturo ; Boto, Martha ; Bouleau, Charles ; Breuer, Léo ; Cahn, Marcelle ; Calder, Alexander ; Callery, Mary ; Calvo, Manuel ; De Caro, Anita ; Carreno, Mario ; Castano ; Charchoune, Serge ; Claisse, Geneviève ; Cruz-Diez, Carlos ; Debré, Olivier ; Delaunay, Sonia ; Demarco, Hugo ; Deyrolle, Jean ; Englert, Rudolf ; Ertan, Simone ; Favrelière, Noël ; Ferlov-Mancoba, Sonia ; Fischli, Hans ; Fruhtrunk, Günter ; Fussell, Michaël ; Garcia-Rossi, Horacio ; Gerstner, Charles ; Getulio, Alviani ; Gilioli, Emilio ; Gisiger, Hansjörg ; Gorin, Jean ; Grate, Eric ; Heurtaux, André ; Hill, Anthony ; Hirst, Barry ; Honegger, Gottfried ; Ibarrola, Agustin ; Kassak, Lajos ; Kelly, Ellsworth ; Knoop, Guitou ; Lardera, Berto ; Le Corbusier ; Lipsi, Morice ; Lohse, Richard ; Mansouroff, Paul ; Morellet, François ; Morisson, Philippe ; Mortensen, Richard ; Nemours, Aurélie ; Olson, Eric ; Osborne ; Parc, Julio Le ; Pasmore, Victor ; Passeron, René ; Peeters, Henk ; Peire, Luc ; Pettoruti, Emilio ; Picelj, Yvan ; Pohl, Uli ; Radou, Othello ; Richter, Hans ; Sakier, George ; Sandfort, Bernard ; Schnabel, Day ; Schoffer, Nicolas ; Seuphor, Michel ; Sobrino, Francisco ; Somaini, Francesco ; Stein, Joël ; Szekely, Pierre ; Teana, Di ; Ternand, Marthe ; Tinguely, Jean ; Tomasello, Luigi ; Vardanega, Gregorio ; Vasarely, Victor ; Vieillard, Roger ; Vieira, Mary ; Youngerman, Jack ; Yvaral, Jean-Pierre
Esquisse d'un Salon, Galerie Denise René, Paris, Mai - Septembre 1963
Frans
boek